SAT0389 Apremilast, an Oral Phosphodiesterase 4 Inhibitor, is Associated with Long-Term (52-Week) Improvements in Enthesitis and Dactylitis in Patients with Psoriatic Arthritis: Results from the Palace 4 Phase 3, Randomized, Controlled Trial. (10th June 2014) - Edwards, C.; Wells, A.; Adebajo, A.; Kivitz, A.; Bird, P.; Shah, K.; Hu, C.; Stevens, R.M.; Aelion, J.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to regulate inflammatory mediators. PALACE 4 compared the efficacy/safety of APR with placebo (PBO) in patients (pts) with active PsA who were DMARD-naïve. Objectives: Evaluate the impact of APR treatment over 52 wks on enthesitis and dactylitis among PALACE 4 pts. Methods: Pts were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30). Pts with <20% reduction from BL in SJC or TJC at Wk 16 were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on the initial APR dose. At Wk 24, all remaining PBO pts were re-randomized to APR20 or APR30. The analysis comprises data from Wks 0-52. Enthesitis was evaluated based on MASES (range 0-13), which indicates the number of painful entheses out of 13 entheses sites. The dactylitis count (range 0-20) is the number of digits (hands and feet) with dactylitis present; each digit is rated as 0 (no dactylitis) or 1 (dactylitis present). Results: At Wk 16, a significantly greater proportion of pts receiving APR20 or APR30 achieved the modified ACR20 response vs PBO (primary endpoint). In pts initially randomized to APR and with enthesitis (n=228) and dactylitis (n=173) at BL, APR was associated with improvements in enthesitis and dactylitis over 52 wks, as evidenced by reductions in the MASES and dactylitis count. At Wk 16, median percent changes in MASES were 0.0% (PBO), -20.0% (APR20; P =0.2948), and -50.0% (APR30; P =0.0008). In pts initially randomized to APR and completing 52 wks, median percent changes in MASES were -66.7% (APR20) and -75% (APR30) (Table); 39.6% (APR20) and 45.9% (APR30) of pts achieved a score of 0, indicating no pain at any of the entheses assessed. Median percent changes in dactylitis count at Wk 16 were -50.0% (PBO), -70.8% (APR20; P =0.0691), and -69.2% (APR30; P =0.1494). In pts initially randomized to APR and completing 52 wks, both doses resulted in a median 100% decrease in the dactylitis count; a dactylitis count of 0 was achieved in 68.6% (APR20) and 68.8% (APR30) of pts. The most common AEs reported during the PBO-controlled period were nausea (12.6%), diarrhea (9.4%), and headache (6.0%). The safety profile of APR for up to 52 wks was similar to that observed with APR for up to 24 wks of treatment (PBO-controlled period). Conclusions: Among pts continuously treated with APR through 52 wks, sustained improvements in both enthesitis and dactylitis were observed in pts with active PsA, who had enthesitis and dactylitis at BL. APR demonstrated an acceptable safety profile and was generally well tolerated for up to 52 wks. Disclosure of Interest: C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc., Roche and Samsung, Consultant for: Celgene Corporation, Pfizer Inc., Roche and Samsung, Speakers bureau: Abbott, Glaxo-Smith Kline, Pfizer Inc., and Roche, A. Wells Grant/research support: Celgene Corporation, A. Adebajo: None declared, A. Kivitz Grant/research support: Amgen, Janssen, Eli Lilly, Novartis, Pfizer Inc., and UCB, Consultant for: Amgen, Janssen, Eli Lilly, Novartis, Pfizer Inc., and UCB, Speakers bureau: Pfizer Inc., P. Bird Grant/research support: Celgene Corporation, K. Shah Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, J. Aelion Grant/research support: Ardea, AstraZeneca, Bristol-MyersSquibb, CelgeneCorporation, CentocorGalapagos, Genetech, GlaxoSmithKline, HumanGenomeSciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, NovoNordisk, PfizerInc., Roche, UCB Biosciences, Sanofi-Aventis, Takeda, and Vertex, Consultant for: Ardea, AstraZeneca, Bristol-MyersSquibb, CelgeneCorporation, CentocorGalapagos, Genetech, GlaxoSmithKline, HumanGenomeSciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, NovoNordisk, PfizerInc., Roche, UCB Biosciences, Sanofi-Aventis, Takeda, and Vertex, Speakers bureau: AbbVie, Amgen, and UCB DOI: 10.1136/annrheumdis-2014-eular.1574